Effects of ribose as an ergogenic aid - Peveler, W. W.; Bishop, P. A.; Whitehorn, E. J. (The Journal of Strength and Conditioning Research, 2006)
The amount of adenosine triphosphate (ATP) stored in the muscle available for immediate use is limited, and once used, must be resynthesized in the muscle. Ribose, a naturally occurring pentose sugar, helps resynthesize ATP for use in muscles. There have been claims that ribose supplements increase ATP levels and improve performance. Other studies have provided mixed results on the effectiveness of ribose as an ergogenic aid at high doses. None of these studies have compared the impact of the recommended dose of ribose on athletes and nonathletes under exercise conditions that are most conducive for effectiveness. The purpose of this study was to evaluate the effectiveness of ribose as an ergogenic aid at the dose recommended for supplements currently on the market during an exercise trial to maximize its efficacy. Male subjects (n = 11) performed 2 trials 1 week apart. Each trial consisted of three 30-second Wingate tests with a 2-minute recovery between each test. Trials were counterbalanced, with 1 trial being performed with 625 mg of ribose and the other with a placebo. Peak power, mean power, and percent decrease in power were recorded during each Wingate test. Repeated-measures analysis of variance (p > 0.05) found no significant differences between ribose and placebo. These results suggest that ribose had no effect on performance when taken orally, at the dose suggested by the distributor.